Pengaruh Gaya Kepemimpinan Guru (Teori X dan Y) terhadap Perilaku Siswa di Kelas pada SMKN 1 Surabaya - Arini Nur Rofidah; Annisa Rehanita; Kumala Sari, Fa'izah Dwi; Atika, Nadiva Zahra; Aprilianto, Adtora; Ananda, Ardhea Dwi; Natasya, Shelma Deva; Roesminingsih, Erny (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of teachers’ leadership styles based on Theory X and Theory Y on students’ behavior in the classroom at SMKN 1 Surabaya. The research employed a quantitative approach using a survey method through the distribution of Likert-scale questionnaires to respondents. Data analysis techniques included validity, reliability, normality, homogeneity, linearity, and simple linear regression tests. The findings indicated that teachers’ leadership styles significantly influence students’ classroom behavior. This was proven by the t-test significance value of 0.004 < 0.05 and the F-test significance value of 0.004 < 0.05. Futhermore, the coefficient of determination value of 13.7% showed that students’ behavior was influenced by teachers’ leadership styles, while the remaining percentage was affected by other factors outside the scope of this study.